Aberrant resting-state regional activity in patients with postpartum depression - Li, Bo; Zhang, Shufen; Li, Shuyan; Liu, Kai; Hou, Xiaoming (Frontiers in Human Neuroscience, 2023)
Background Postpartum depression (PPD) is a common disorder with corresponding cognitive impairments such as depressed mood, memory deficits, poor concentration, and declining executive functions, but little is known about its underlying neuropathology. Method A total of 28 patients with PPD and 29 healthy postpartum women were recruited. Resting-state functional magnetic resonance imaging (rs-fMRI) scans were performed in the fourth week after delivery. Individual local activity of PPD patients was observed by regional homogeneity (ReHo) during resting state, and the ReHo value was computed as Kendall's coecient of concordance (KCC) and analyzed for differences between voxel groups. Correlations between ReHo values and clinical variables were also analyzed. Result Compared with healthy postpartum women, patients with PPD exhibited significantly higher ReHo values in the left precuneus and right hippocampus. ReHo value was significantly lower in the left dorsolateral prefrontal cortex (dlPFC) and right insula. Furthermore, ReHo values within the dlPFC were negatively correlated with the Edinburgh PPD scale (EPDS) score. The functional connectivity (FC) of the right hippocampus to the left precuneus and left superior frontal gyrus (SFG) was stronger in patients with PPD than that in controls. Conclusion The present study provided evidence of aberrant regional functional activity and connectivity within brain regions in PPD, and it may contribute to further understanding of the neuropathology underlying PPD.